Correction: Spenger et al. Glutaric Aciduria Type I Missed by Newborn Screening: Report of Four Cases from Three Families. Int. J. Neonatal Screen. 2021, 7, 32 - Johannes Spenger; Esther M. Maier; Katharina Wechselberger; Florian Bauder; Melanie Kocher; Wolfgang Sperl; Martin Preisel; Katharina A. Schiergens; Vassiliki Konstantopoulou; Wulf Röschinger; Johannes Häberle; Thomas Schmitt-Mechelke; et al. (MDPI AG, 2021)
There was an error in the original publication [...]